2018
DOI: 10.1111/jspn.12229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family nutrition and physical activity screening for obesity risk in school‐age children

Abstract: Purpose An obesogenic home environment is a major contributor to overeating and sedentariness in school‐aged children, as children have less autonomy during this phase of development and are influenced by family environmental cues. The purpose of this study was to implement a screening tool at a low socioeconomic elementary school clinic to identify children at risk of developing obesity and provide standardization for practitioners on educating parents regarding child obesity risk factors. Design and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…To maintain healthy weight and avoid unhealthy weight gain, it is important to balance energy intake through healthy foods and beverages and energy expenditure with basal metabolic rate (BMR) and PA. Previous studies reported that children with higher BMI had unhealthier EH and more sedentary lifestyle habits [ 10 ]. For example, it has been shown that obese and overweight pupils more often skipped breakfast [ 11 ], consumed more ultra-processed calorie dense foods [ 12 ] and had lower MVPA levels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain healthy weight and avoid unhealthy weight gain, it is important to balance energy intake through healthy foods and beverages and energy expenditure with basal metabolic rate (BMR) and PA. Previous studies reported that children with higher BMI had unhealthier EH and more sedentary lifestyle habits [ 10 ]. For example, it has been shown that obese and overweight pupils more often skipped breakfast [ 11 ], consumed more ultra-processed calorie dense foods [ 12 ] and had lower MVPA levels [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for these associations is that children who have experienced maternal excessive GWG are at increased risk of obesity due to developmental programming in utero as well as exposure to the same obesogenic environment and lifestyle from the mother, such as high‐caloric food intake and low physical activity 15 . Children over 2 years of age have already incorporated familiar habits and behaviours that may influence their nutritional status 30 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, if these two conditions were present among children and adolescents, a sedentary lifestyle could be avoided in 56.5% and 48.2% of exposed cases, respectively. An obesogenic home environment is known to be an important factor in overeating and promoting a sedentary life- Hence the need for this contemporary society to become aware of the influence of parents and family members as role models for children and adolescents to adopt healthy lifestyles behaviors (Herbenick et al, 2018). A Canadian study confirms the positive influence that physical activity modeling and parental support have on the child's physical activity level, whether both conditions are fulfilled or only one of the two (Garriguet, Colley, & Bushnik, 2017).…”
Section: Discussionmentioning
confidence: 99%